Pencatatan Laporan Keuangan Berbasis Digital Untuk Usaha Mikro, Kecil dan Menengah - Kersna Minan; Liza Novietta; Ruswan Nurmadi (Insight Power (Kekuatan Wawasan), 2022)
The problem that is often faced by Medium, Small and Micro Enterprises (MSMEs) is the lack of understanding of the preparation of financial statements, so they do not know for sure whether the capital they have has been effectively used and the efficiency of operating expenses, so that they can generate maximum profit. Lack of working capital and difficulties in obtaining additional profits from banking institutions that have special requirements for the provision of small business capital, such as the existence of financial reporting according to the standards that have been set for MSMEs are also problems faced. Higher Education Institutions, through community service activities, must assist the government in providing socialization and training to MSME actors on how to prepare financial reports, especially through digital-based applications, in order to make it easier for MSME actors and adjustments to the times. This community service is carried out for MSME actors in Medan Labuhan District. By carrying out this activity, it is hoped that it will increase the prosperity of the MSME community.Keywords: Community Service, MSMEs, Financial Reporting, Digital Application, Community Prosperity